A new horsehair worm, Chordodes formosanus sp. n. (Nematomorpha, Gordiida) from Hierodula mantids of Taiwan and Japan with redescription of a closely related species, Chordodes japonensis - Ming-Chung Chiu; Chin-Gi Huang; Wen-Jer Wu; Shiuh-Feng Shiao (ZooKeys, 2011)
A new species of horsehair worm, Chordodes formosanus sp. n., is described and compared to a closely related species, C. japonensis. Although both species possess the same six cuticular structures of areoles on the surface, the significantly longer filaments on the female crowned areoles can be used as diagnostic characters for the new species. The different taxonomic status of these two species was also confirmed after analyzing the partial cytochrome oxidase subunit I sequence, and the mantid hosts, which are respectively limited to the genus Tenodera for C. japonensis and Hierodula for C. formosanus sp. n. In addition, the immature stages of eggs and larvae of the new species are also described and discussed in detail.